Magnesium disturbances in critically ill children - Selma Amar; Sofia Martín Acedo; Santiago Rodríguez-Tubio; Claudia Olalla; Cristina De Ángeles; José Ángel Zamorano; Rosario Pérez; Blanca Ramírez; Jesús López-Herce; Rafael González (Scientific Reports)
Abstract To analyse the prevalence of magnesium disturbances in children admitted to the Paediatric Intensive Care Unit (PICU) and its relationship with complications and mortality. Single-center, observational, retrospective study. Children with measured serum magnesium levels were included. Clinical, analytical, treatment data, clinical severity scores (Functional Status Scale, Paediatric Risk of Mortality, Paediatric Logistic Organ Dysfunction and Paediatric Multiple Organ Dysfunction Score) at admission and during PICU admission, mortality and duration of admission were recorded. A cohort of 200 children (57% male) with a median age of 55 months (interquartile range 8 months to 11 years) were included. Six children (3%) presented initial hypomagnesemia and 26 (13%) presented hypomagnesemia during admission. Hypomagnesemia during admission was significantly associated with the presence of acute kidney injury (AKI) (p = 0.038), shock (p = 0.003), and extracorporeal membrane oxygenation (ECMO) (p = 0.046). Patients with hypomagnesemia had a higher mortality (15.4% versus 1.7%) (p = 0.006). 64 children (32%) presented initial hypermagnesemia, and 89 (44.5%) presented hypermagnesemia during admission. Hypermagnesemia during admission was significantly associated with heart surgery (p < 0.001), without significant differences in mortality (p = 0.702). Hypomagnesemia and hypermagnesemia are common among children admitted to the PICU. Hypomagnesemia during admission was associated with AKI, shock, ECMO and mortality. Hypermagnesemia during admission was associated with cardiac surgery but not with mortality.